Migration und Polizei Auswirkungen der Zuwanderung auf die Organisation und Diversität der deutschen Polizei - Vera, Antonio; Behr, Rafael; Brussig, Martin; Weiß, Anja (Sicherheit. Polizeiwissenschaft und Sicherheitsforschung im Kontext, 2022)
This anthology presents the results of a research project that used qualitative empirical methods to analyse processes of institutional change with which the police respond to migration-related challenges. The contributions the book contains deal with diversity management concerning police personnel. They study how the police's organisational culture responds to migration-related challenges. The book's findings show that decades of migration have led to considerable changes in the German police. The authors are experts in migration and/or police research and have a background in sociology and economics. With contributions by Alexander Auth; Prof. Dr. Rafael Behr; Prof. Dr. Martin Brussig; Alexandra Graevskaia, M.A.; Annelie Molapisi, M.A.; Benedikt Müller, M.A.; Verena Thomas, M.A.; Prof. Dr. Dr. Antonio Vera and Prof. Dr. Anja Weiß.